Women & art: a history of women painters and sculptors from the renaissance to the 20th century - Fine, Elsa Honig (Allanheld & Schram/Prior, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Women artists: recognition and reappraisal from the early Middle Ages to the twentieth century - Petersen, Karen; Wilson, J. J. (Harper colophon books ; CN 387, 1976)
Commentary on and photographs of sculpted and painted images of women created by women shed light upon feminine self-perceptions and the contributions of women artists through the centuries
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Women painters of the world: from the time of Caterina Vigri, 1413-1463, to Rosa Bonheur and the present day - Sparrow, Walter Shaw (Hacker Art Books, 1976)
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques

Our hidden heritage: five centuries of women artists - Tufts, Eleanor (Paddington Press, 1974)
Our hidden heritage: five centuries of women artists unearths an unheralded legacy of art treasures by women artists. THrough individual biographies, the lives and work of twenty-two women artists are authoritatively described by Eleanor Tufts. These exciting portrayals provide new insights into the lives and works, the frustrations and successes of these talented women, as well as into their relationships with their contemporaries, husbands, freinds and families. Over 125 full-page reproductions of their works from major collections throughout the world demonstrate the variety and enduring quality of their art. Their lives and their work were as diverse as their cultures and their times.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques